Vitamin D concentration in the blood of women with twin pregnancies and in the umbilical cord blood of newborns in relation to environmental factors - Wierzejska, Regina Ewa; Szymusik, Iwona; Bomba-Opoń, Dorota; Rzucidło-Szymańska, Iga; Wojda, Barbara; Biskupski-Brawura-Samaha, Robert (Frontiers in Nutrition, 2024)
Background There is a huge gap in the knowledge of the body’s nutrient resources in women with multiple gestations. Due to the increased demand hypothesis and taking into account common vitamin D deficits in women with singleton pregnancies, this issue should also be investigated in twin pregnancies. This study evaluated blood vitamin D concentration in women with twin pregnancies and in the umbilical cord blood of their newborns as well as analyzed environmental factors that may affect the level of this nutrient. Methods The study included 56 women with twin pregnancies. Venous blood samples were collected from the women before delivery and umbilical cord blood at delivery to determine the total 25(OH)D concentration. The women were interviewed by a dietitian to collect data on their diet and lifestyle. Results The average maternal 25(OH)D concentrations were 38.4 ± 11.0 ng/mL vs. 23.7 ± 6.1 ng/mL determined in the umbilical cord blood of the newborns. The concentration of 25(OH)D in the umbilical cord blood was strongly correlated with the concentration in the mother (p < 0.001). Vitamin D deficiency was found in 7% of women and 21% of newborns. Factors increasing the risk of too low 25(OH)D concentration in the mothers were age below 27 years (p = 0.002) and short duration of pregnancy (p = 0.011). In newborns, the risk factors included low maternal concentrations (p < 0.001) and delivery before 36 weeks of gestation (p = 0.008). The mean cord blood 25(OH)D levels were almost identical in both twins and amounted to 24.0 ± 6.1 ng/mL in the first-born and 23.4 ± 6.1 ng/mL in the second-born infant. Vitamin D supplementation was declared by 98% of the women, with 85% taking ≤2,000 IU vitamin D daily. Conclusion Only a small percentage of women with twin pregnancies presented with vitamin D deficiency, which was probably related to the widespread supplementation of this nutrient. It can therefore be assumed that a dose of 2,000 IU vitamin D currently recommended for pregnant women may also be appropriate for twin gestations, although further research is required to validate this finding.